Covid-19 and acute conjunctivitis: Controversial data from a tertiary refferral Italian center. Issue 6 (November 2021) - D'Amico Ricci, Giuseppe; Del Turco, Claudia; Belcastro, Elena; Palisi, Marco; Romano, Mario R; Pinna, Antonio; Panico, Claudio; La Spina, Carlo
Purpose: Although acute conjunctivitis has been listed from the beginning as a possible sign of COVID-19, the likelihood of this association remains unclear. The aim of this study was to investigate the relationship between COVID-19 and conjunctivitis. Methods: In this retrospective, observational study, we recruited all patients with signs and symptoms of acute conjunctivitis seen at the Eye Emergency Department (ED), Turin Eye Hospital, between 01/01/2020 and 12/05/2020 and cross-checked our data with the Piedmont Region online COVID-19 registry in the same period. Results: Among 10, 065 patients seen at our ED during the timespan considered, 88 underwent a nasopharyngeal swab (NS) for SARS-CoV-2 detection within 4 weeks before/after our examination. On average, NS was performed −0.72 ± 1.8 weeks before/after eye examination. Of the 77 patients with a negative NS, 26 (33.8%) had a diagnosis of acute conjunctivitis, whereas the remaining 51 (66.2%) had other eye disorders. Among the 11 patients with COVID-19, 7 (63, 6%) had a diagnosis of acute conjunctivitis. We found a non-statistically significant increase in NS positivity rate (21.2%) among cases examined at our ED for acute conjunctivitis, compared to the NS positivity rate (7.3%) in patients examined for all other eye conditions ( p  = 0.092). The Odds Ratio of having a positive NS in patients with acute conjunctivitis was 3.43 (95% I.C. = 0.9–12.8, p  = 0.06). Considering online-registry data of Turin population during the same time-span, among 2441 positive NS cases only 27 (1.1%) presented with acute conjunctivitis. Conclusion: Our results do not reveal a statistically significant correlation between COVID-19 and acute conjunctivitis. Synopsis: The present study analyzes retrospectively data from a tertiary eye referral center to investigate the relationship between COVID-19 infection and conjunctivitis.